Lack of TRPM5-Expressing Microvillous Cells in Mouse Main Olfactory Epithelium Leads to Impaired Odor-Evoked Responses and Olfactory-Guided Behavior in a Challenging Chemical Environment - Lemons, Kayla (eNeuro, 2017)
The mammalian main olfactory epithelium (MOE) modifies its activities in response to changes in the chemical environment. This process is essential for maintaining the functions of the olfactory system and the upper airway. However, mechanisms involved in this functional maintenance, especially those occurring via paracrine regulatory pathways within the multicellular MOE, are poorly understood. Previously, a population of non-neuronal, transient receptor potential M5-expressing microvillous cells (TRPM5-MCs) was identified in the MOE, and the initial characterization of these cells showed that they are cholinergic and responsive to various xenobiotics including odorants at high concentrations. Here, we investigated the role of TRPM5-MCs in maintaining olfactory function using transcription factor Skn-1a knockout (Skn-1a(-/-)) mice, which lack TRPM5-MCs in the MOE. Under our standard housing conditions, Skn-1a(-/-) mice do not differ significantly from control mice in odor-evoked electro-olfactogram (EOG) responses and olfactory-guided behaviors, including finding buried food and preference reactions to socially and sexually relevant odors. However, after a 2-wk exposure to high-concentration odor chemicals and chitin powder, Skn-1a(-/-) mice exhibited a significant reduction in their odor and pheromone-evoked EOG responses. Consequently, their olfactory-guided behaviors were impaired compared with vehicle-exposed Skn-1a(-/-) mice. Conversely, the chemical exposure did not induce significant changes in the EOG responses and olfactory behaviors of control mice. Therefore, our physiological and behavioral results indicate that TRPM5-MCs play a protective role in maintaining the olfactory function of the MOE.